2014
DOI: 10.1002/celc.201402194
|View full text |Cite
|
Sign up to set email alerts
|

The Mtr Pathway of Shewanella oneidensis MR‐1 Couples Substrate Utilization to Current Production in Escherichia coli

Abstract: Introducing an electronic interface into Escherichia coli will allow its enormous synthetic biology toolkit to be leveraged in bioelectrochemical applications. While E. coli expressing the Mtr pathway of Shewanella oneidensis MR‐1 transfer electrons to an anode, it has remained unclear if this current production alters the intracellular state of E. coli, which is a critical requirement for bioelectronic technologies. Here we address this by characterizing current production in Mtr‐expressing E. coli and its ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 15 publications
(7 reference statements)
0
79
0
Order By: Relevance
“…Microbial metabolism of electrons that are not associated with a chemical element, that is, 'free' electrons, is an intriguing metabolic capacity that has been primarily investigated in insoluble metalreducing microorganisms, such as Shewanella or Geobacter species (Bond and Lovley, 2003;Hartshorne et al, 2009;Coursolle et al, 2010;Clarke et al, 2011;Lovley, 2012;Liu et al, 2014;Malvankar and Lovley, 2014;Pirbadian et al, 2014;TerAvest et al, 2014). In addition to these anodic microbial processes, recent studies have revealed that some microorganisms can take up 'free' cathodic electrons from conductive minerals during interspecies electron transfer (Kato et al, 2012) or from abiotically reduced surfaces such as deep sea hydrothermal vent chimneys (Nakamura et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial metabolism of electrons that are not associated with a chemical element, that is, 'free' electrons, is an intriguing metabolic capacity that has been primarily investigated in insoluble metalreducing microorganisms, such as Shewanella or Geobacter species (Bond and Lovley, 2003;Hartshorne et al, 2009;Coursolle et al, 2010;Clarke et al, 2011;Lovley, 2012;Liu et al, 2014;Malvankar and Lovley, 2014;Pirbadian et al, 2014;TerAvest et al, 2014). In addition to these anodic microbial processes, recent studies have revealed that some microorganisms can take up 'free' cathodic electrons from conductive minerals during interspecies electron transfer (Kato et al, 2012) or from abiotically reduced surfaces such as deep sea hydrothermal vent chimneys (Nakamura et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Further improvement was achieved by co-expressing CymA to circumvent the unnatural interaction between MtrA and NapC, an interaction that serves as a bottleneck in shuttling electrons from the quinone pool to the MtrCAB complex in E. coli . The resulting cymA-mtrCAB E. coli strain reduced both solid Fe 2 O 3 65 and an electrode 66 at a significantly faster rate than the strain expressing only MtrCAB. Moreover, cyclic voltammetry of these strains showed that re-reduction of MtrCAB was faster with co-expression of CymA, confirming the importance of appropriate protein-protein interactions 65 .…”
Section: Overcoming Challenges In the Bioengineering Of Extracellumentioning
confidence: 96%
“…Though the expression of MtrA, MtrB, and MtrC is sufficient to impart a cell with exoelectrogenicity, the co-expression of CymA was found to improve overall extracellular electron transfer in E. coli 61,66 . The introduction of CymA is believed to facilitate electron transfer between endogenous E. coli proteins and the heterologous MtrA.…”
Section: Challenges and Outlook On Technological Improvementsmentioning
confidence: 99%
“…[7][8][9] The successful genetic incorporation of extracellular electron transfer (EET) proteins like c-type cytochromes from Shewanella oneidensis for enhanced electroactivity renders E. coli excellent for MES. [10][11][12] In particular,t he utilized E. coli strain JG622 LbADH expressesc ytochromes MtrA, CymA, and STC from S. oneidensis forE ET,h eme exporterp roteins ccmA-Hf or cytochrome maturation,a sw ell as an alcohol dehydrogenase from Lactobacillus brevis (LbADH). [6,[13][14][15] LbADH is aN ADPH-dependento xidoreductase, which catalyzes the enantioselective reduction of bulky ketones to (R)-alcohols.…”
Section: Introductionmentioning
confidence: 99%